Tectonic evolution of the Neoproterozoic Tandilia sedimentary cover, Argentina: New evidence of contraction and extensional events in the southwest Gondwana margin - Hernández, Mariano (2017)
At the northwestern portion of the Tandilia System, a detailed structural analysis on the Precambrian sedimentary units exposed in the quarries of the Olavarría-Sierras Bayas area was carried out. These units exhibit deformational structures of several scales, from centimeters to hundreds of meters. The hundreds of meters scale involves E-W- and NW-SE-trending normal faults and NW-SE- and NE-SW-trending contractional folds. The centimeters to meters scale involves veins, joints, normal faults, shear fractures and stylolites, with a prevailing ∼ E-W to NW-SE trend. All these structures were formed by two major tectonic events. The first was the folding event at ∼580 Ma, with NNE-SSW to NE-SW and NW-SE direction of contraction. The second was the extensional faulting event, given by the widespread NNE-SSW-directed extension event during the Atlantic Ocean opening (Jurassic-Cretaceous). Both major events would have been controlled by the reactivation of basement anisotropies. These major tectonic events controlled the deformation of the Precambrian sedimentary cover of the Tandilia system, leading to an economically important aspect in the mining development of the Olavarría-Sierras Bayas area.